18F-FDG-PET hypometabolism as a predictor of favourable outcome in epilepsy surgery: protocol for a systematic review and meta-analysis. Issue 10 (6th October 2022) - Courtney, Merran R; Antonic-Baker, Ana; Sinclair, Benjamin; Nicolo, John-Paul; Neal, Andrew; Law, Meng; Kwan, Patrick; O'Brien, Terence J; Vivash, Lucy
Abstract : Introduction: A substantial proportion of patients who undergo surgery for drug resistant focal epilepsy do not become seizure free. While some factors, such as the detection of hippocampal sclerosis or a resectable lesion on MRI and electroencephalogram-MRI concordance, can predict favourable outcomes in epilepsy surgery, the prognostic value of the detection of focal hypometabolism with 18 F-fluorodeoxyglucose positive emission tomography ( 18 F-FDG-PET) hypometabolism is uncertain. We propose a protocol for a systematic review and meta-analysis to examine whether localisation with 18 F-FDG-PET hypometabolism predicts favourable outcomes in epilepsy surgery. Methods and analysis: A systematic literature search of Medline, Embase and Web of Science will be undertaken. Publications which include evaluation with 18 F-FDG-PET prior to surgery for drug resistant focal epilepsy, and which report ≥12 months of postoperative surgical outcome data will be included. Non-human, non-English language publications, publications with fewer than 10 participants and unpublished data will be excluded. Screening and full-text review of publications for inclusion will be undertaken by two independent investigators, with discrepancies resolved by consensus or a third investigator. Data will be extracted and pooled using random effects meta-analysis, with heterogeneity quantified using the I 2 analysis. Ethics and dissemination: Ethics approval is not required. Once complete, the systematic review will be published in a peer-reviewed journal. PROSPERO registration number: CRD42022324823.